Carbon coated hierarchical porous MoO2 nanoflowers as high-performance anodes in lithium-ion batteries - Tang, Shasha (2020)
Carbon-coated hierarchical porous MoO2 nanoflowers are synthetized via a template-free solvothermal technique and investigated as anodes in lithium-ion batteries (LIBs). Such hybrid porous materials possess high porosity and a conductive layer, which have superior lithium ion/electron transport. The voids inside the structure can accommodate huge volume expansion and relieve the stress. The relative MoO2 electrodes present a high reversible capacity of 784.7 mA h g −1 after 60 cycles (707.7 mA h g−1 after 120 cycles for 200 mA g−1) and high coulumbic efficiency (above 98% over 120 cycles). Our study can easily be extended to other materials with a similar hierarchical structure in view of their application in LIBs.